ANALISIS HUKUM PENYERTAAN “DELLNEMING” DALAM PENEGAKAN HUKUM PIDANA PEMILU : EVALUASI PEMILU 2019 DAN PROYEKSI PEMILU 2024 - Kurnia, Yusup (Bawaslu Provinsi Jawa Barat, 2021)
The general elections and elections in 2024 will be the first experiences because they will be held concurrently in the same year. Reflecting on the implementation of the 2019 elections, the Integrated Law Enforcement Center's (Gakkumdu) discussion of problems has a significant impact on the process of enforcing the Election Criminal Law. The issue stems from the process of completing the elements of election crime. Substantive law enforcement is important to put forward, considering that, empirically, in the 2019 elections, it has produced a precedent in the application of the